2018
DOI: 10.1002/nsg.12025
|View full text |Cite
|
Sign up to set email alerts
|

Time‐lapse laboratory tests to monitor multiple phases of DNAPL in a porous medium

Abstract: A B S T R A C TA soil contaminated by dense non-aqueous phase liquids generally exhibits variation of electrical permittivity and resistivity over time. In this paper, we relate photo images with results of electrical resistivity tomography, induced polarization tomography, and ground-penetrating radar survey in a laboratory-controlled test, where a cell, filled with grained-glass beads contaminated with HFE-7100 (hydrofluoroether) and under saturated conditions, was used. The aim was to find robust links betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…The use of GB also prevents the occurrence of unexpected phenomena such as adsorption during the experiment. The relative permittivity of a GB pack is 5.9 (Orlando and Palladini, 2019). The complex resistivity of the medium was measured with SIP using SIP-lab IV manufactured by Radic Research in Germany.…”
Section: Methodsmentioning
confidence: 99%
“…The use of GB also prevents the occurrence of unexpected phenomena such as adsorption during the experiment. The relative permittivity of a GB pack is 5.9 (Orlando and Palladini, 2019). The complex resistivity of the medium was measured with SIP using SIP-lab IV manufactured by Radic Research in Germany.…”
Section: Methodsmentioning
confidence: 99%
“…(2014). Orlando and Palladini (2019) carried out a series of laboratory tests to study how resistivity and permittivity vary in a 2D cell in a multiphase (two‐phase) system. The contamination they used was HFE‐7100 (hydrofluoroether) in saturated (with pure, dissolved and gaseous phases) grained GB porous media.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, Orlando and Renzi (2015) studied how electrical resistivity varies in ground due to the existence of DNAPL in a laboratory study. Like Orlando and Palladini (2019), they used a GB‐packed medium contaminated with HFE‐7100 in a saturated condition. They found that different DNAPL phases have different impacts on the physico‐chemical characteristics of the contaminated medium.…”
Section: Introductionmentioning
confidence: 99%